2023
DOI: 10.1089/lgbt.2022.0187
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Pain in Transgender People Using Testosterone Therapy

Abstract: Purpose: This descriptive study aimed to assess the characteristics of pelvic pain and explore predictive factors for pelvic pain in transgender (trans) individuals using testosterone therapy. Methods: An online cross-sectional survey was open between August 28, 2020, and December 31, 2020, to trans people presumed female at birth, using testosterone for gender affirmation, living in Australia, and >16 years of age. The survey explored characteristics of pelvic pain fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 44 publications
(45 reference statements)
0
12
0
Order By: Relevance
“…When androgens do reduce pain, the reduction coincides with its attenuating effects on inflammation ( 151 ). However, it has been shown that pelvic pain in transgender men often occurs after initiation of testosterone therapy ( 152 ). Given the known androgen sensitivity of the pelvic floor musculature ( 153 ), further research into pelvic floor muscle dysfunction is warranted.…”
Section: Hormone Replacement Therapy (Hrt) In Adultsmentioning
confidence: 99%
“…When androgens do reduce pain, the reduction coincides with its attenuating effects on inflammation ( 151 ). However, it has been shown that pelvic pain in transgender men often occurs after initiation of testosterone therapy ( 152 ). Given the known androgen sensitivity of the pelvic floor musculature ( 153 ), further research into pelvic floor muscle dysfunction is warranted.…”
Section: Hormone Replacement Therapy (Hrt) In Adultsmentioning
confidence: 99%
“…Testosterone therapy, which is commonly used during gender transition, can influence the symptoms and presentation of endometriosis in transgender men ( 12 ). The hormonal changes brought about by testosterone can mask or alter typical symptoms, such as changes in menstrual patterns or pelvic pain ( 13 ). Healthcare providers must be knowledgeable about these potential variations to ensure accurate diagnosis.…”
Section: Challenges In Diagnosismentioning
confidence: 99%
“…A significant number of transgender individuals seek hysterectomy and/or oophorectomy as part of their gender affirmation process or due to persistent pelvic pain or abnormal bleeding. Among those who underwent hysterectomy, 72% reported experiencing relief from pelvic pain symptoms following the procedure ( 13 ). This surgery effectively stops ongoing menstruation, which is particularly prevalent in those experiencing pain after beginning testosterone therapy.…”
Section: Tailored Management Strategiesmentioning
confidence: 99%
“…10 I was surprised to learn that testosterone use itself can lead to pelvic pain through pelvic floor dysfunction due to the anabolic effect of the hormone. 11 Before an aside from my preceptor in clinic that day, no one had ever mentioned testosterone as a potential etiology of pelvic pain. As a result, this was not something originally on my differential when I saw that first patient.…”
mentioning
confidence: 99%
“…10 I was surprised to learn that testosterone use itself can lead to pelvic pain through pelvic floor dysfunction due to the anabolic effect of the hormone. 11…”
mentioning
confidence: 99%